The Value of Dysregulated LncRNAs on Clinicopathology and Survival in Non-Small-Cell Lung Cancer: A Systematic Review and Meta-Analysis - Wang, Juan; Han, Xu; Yuan, Ye; Gu, Hao; Liao, Xing; Jiang, Miao (Frontiers in Genetics, 2022)
Background: There is growing evidence that a number of lncRNAs are involved in the pathogenesis of non-small-cell lung cancer (NSCLC). However, studies on lncRNA expression in NSCLC patients are far from conclusive. Therefore, we performed a systematic review of such studies to collect and examine the evidence on the potential role of lncRNAs in the development of NSCLC. Methods: We systematically searched seven literature databases to identify all published studies that evaluated the expression of one or more lncRNAs in human samples with NSCLC (cases) and without NSCLC (controls) from January 1, 1995 to May 24, 2021. Quality assessment of studies was conducted by using the “Quality in Prognosis Studies” (QUIPS) tool, and the heterogeneity across studies was analyzed with the I-squared statistic and chi-square-based Q-tests. Either fixed or random-effect meta-analysis was performed to summarize effect size to investigate the association between lncRNA expression and overall survival (OS), disease-free survival (DFS), progression-free survival (PFS), and clinicopathological features. The R statistical software program was used to conduct standard meta-analysis. Results: We finally obtained 48 studies with 5,211 patients included in this review after screening. Among the 48 lncRNAs, 38 lncRNAs were consistently upregulated, and 10 were deregulated in patients with NSCLC compared with the control groups. The upregulated lncRNAs were positively associated with histological type: study number (n) = 18, odds ratio (OR) = 0.78, 95% CI: 0.65–0.95 and OR = 1.30, 95% CI: 1.08–1.57, p < 0.01; TNM stages: n = 20, OR = 0.41, 95% CI: 0.29–0.57 and OR = 2.44, 95% CI: 1.73–3.44, p < 0.01; lymph node metastasis: n = 29, OR = 0.49, 95% CI: 0.34–0.71 and OR = 2.04, 95% CI: 1.40–2.96, p < 0.01; differentiation grade: n = 6, OR = 0.61, 95% CI: 0.38–0.99 and OR = 1.63, 95% CI: 1.01–2.64, p < 0.01; distant metastasis: n = 9, OR = 0.37, 95% CI: 0.26–0.53 and OR = 2.72, 95% CI: 1.90–3.90, p < 0.01; tumor size: n = 16, OR = 0.52, 95% CI: 0.43–0.64 and OR = 1.92, 95% CI: 1.57–2.34, p < 0.01; and overall survival [n = 38, hazard ratio (HR) = 1.79, 95% CI = 1.59–2.02, p < 0.01]. Especially, five upregulated lncRNAs (linc01234, ZEB1-AS1, linc00152, PVT1, and BANCR) were closely associated with TNM Ⅲa stage (n = 5, OR = 4.07, 95% CI: 2.63–6.28, p < 0.01). However, 10 deregulated lncRNAs were not significantly associated with the pathogenesis and overall survival in NSCLC in the meta-analysis (p ≥ 0.05). Conclusion: This systematic review suggests that the upregulated lncRNAs could serve as biomarkers for predicting promising prognosis of NSCLC. The prognostic value of downregulated lncRNA in NSCLC needs to be further explored. Systematic Review Registration: (http://www.crd.york.ac.uk/PROSPERO).identifier CRD42021240635.